Increased CO2 and iron availability effects on carbon assimilation and calcification on the formation of Emiliania huxleyi blooms in a coastal phytoplankton community - Lorenzo, M. Rosario; Íñiguez Moreno, Concepción; Egge, Jorun K.; Larsen, Aud; Berger, Stella A.; García-Gómez, Candela; Segovia-Azcorra, María (Environmental and Experimental Botany, 2018)
In the present work, we exposed a natural phytoplankton community to either present (390-μatm, LC) or future CO2 levels predicted for year-2100 (900-μatm, HC) combined with ambient (4.5 nmol L−1, −DFB) or high (12 nmol L−1, +DFB) dissolved iron (dFe) levels, during 25 days by using mesocosms. We report on changes in carbon assimilation processes (acquisition, fixation, and calcification) of the phytoplankton community due to increased dissolved CO2 and dFe and to the interaction of both factors. The isotopic disequilibrium assay results showed that inorganic carbon (Ci) acquisition by the community was unaffected by CO2 and Fe availability. The main Ci source for photosynthesis was bicarbonate and external carbonic anhydrase activity was only detected at the beginning of the experiment, suggesting a relevant role for bicarbonate transporters in the phytoplankton community developed in all treatments. However, there was a significant effect of both factors on particulate organic carbon (POC) content, particulate calcium production and carbon fixation rates. Increased dFe at LC conditions led to the highest values of carbon fixation and POC of all treatments, promoting a massive Emiliania huxleyi bloom. This response was not observed in the HC treatments. The latter indicates a negative impact of increased CO2 on the formation of E. huxleyi blooms, in agreement with the observed significant reduction in calcium production under HC. Our results suggest that ocean acidification can decrease primary production under iron-replete conditions in E. huxleyi blooming areas, affecting the biological carbon pump in coastal ecosystems.